Enquiry into Cooperation Between Master’s IT Programme and Companies - Hakala, I.; Laine, S.; Myllymäki, M. (Elektronika ir Elektrotechnika, 2010)
Cooperation between and with companies is emphasized when education is arranged for adults who study alongside their work. To bring the needs of companies into attention, a Verkotut project was launched. Its purpose is to improve the integration of education in information technology and work life. One of the central activities in the project was a company survey, the results of which will orientate the work of the project later on. The survey mapped out the importance of employees’ educational level and of employees’ general skills and substance competence areas to companies, as well as matters related to the integration of work and study. This article focuses on the examination of the results of the company survey.